Assessing focused wave applicability on a coupled aero-hydro-mooring FOWT system using CFD approach. (15th November 2021) - Zhou, Yang; Xiao, Qing; Peyrard, Christophe; Pan, Guang
Abstract: The present study examines the wave type and wave steepness impacts onto the floating offshore wind turbine (FOWT) hydro/aerodynamics. With the aid of using a high-fidelity aero-hydro-mooring CFD solver, the current modelling focuses on the analysis of NREL 5 MW semi-submersible FOWT dynamic motion response, tension load of the mooring line, wind turbine thrust, power output and tower base bending moment. Totally, three types of waves, i.e., focused wave, irregular wave and reconstructed focused wave are adopted to examine the wave type impacts on FOWT performance. Our results find that, given a same wave spectrum, a significant difference is observed for the floater motion response prediction between a focused wave and an irregular wave. However, with the use of the reconstructed focused wave, the results show very similar FOWT hydrodynamic characteristics as those obtained with the irregular wave, indicating that the reconstructed focused wave can be an alternative of the irregular wave for extreme wave studies. Moreover, nonlinear effect is well captured for various wave steepness tested, which is revealed by the occurrence of wave diffraction and large wave run-ups near the side columns. The examination on FOWT aerodynamics found that both wave type and wave steepness have little impact on turbine aerodynamic performance which is evident by a close agreement of thrust and power prediction under different incident waves. Highlights: Investigating the effect of wave type and wave steepness on the floating offshore wind turbine (FOWT) structure by using a high-fidelity CFD method. Presenting the first investigation of the correlations between the focused wave and irregular wave on a moored floating structure. Observing a significant difference for the floater hydrodynamic charateristics subjected to different wave types. Indicating the reconstructed focused wave can be an alternative of the irregular wave for extreme wave studies.